Resilient food systems and climate, peace and security interplay in Kenya. Climate security hotspots and food security insights. - Belli, Anna; Kenduiywo, Benson Kipkemboi; Chepngetich, Brenda; Pacillo, Grazia; Läderach, Peter (2023)
Kenya grapples with climate change challenges, experiencing erratic weather patterns, prolonged droughts, and floods that significantly limit agricultural productivity and natural resources availability. This not only exacerbates food insecurity but also heightens the potential for conflicts. The Arid and Semi-Arid Lands (ASALs), especially in northern counties like Turkana, are particularly vulnerable, experiencing a surge in climate-induced food shortages compounded by escalating conflict risks. The hotspots analysis presented in this factsheet highlights the critical convergence of extreme climate and conflict events, coupled with various food insecurity indicators. Alarmingly, counties such as Turkana, Tana River, and Lamu exhibit a co-occurrence of high conflict, drought stress, and poor-to-borderline Food Consumption Scores (FCS). Mandera, Meru, and Kajiado report crisis or emergency levels of reduced Coping Strategies Index (rCSI), aligning with both climatic stresses and conflict risks. Examination of crisis-to-emergency Livelihood Coping Strategies (LCS) and the percentage of individuals in Integrated Food Security Phase Classification (IPC) Phase 3 and above reveals severe situations in counties like Turkana, Marsabit, Mandera, Garissa, Wajir, Tana River, and Isiolo, compounded by escalating conflict risks and drought stress. Specific regions, including Turkana, Marsabit, Mandera, and Wajir, persistently grapple with high conflict and severe drought, presenting ongoing challenges. Notably, Turkana emerges as the most vulnerable, marked by borderline FCS, emergency rCSI, and a significant share of population facing alarming food security phases. Recognizing data gaps during hotspot mapping underscores the imperative for enhanced data collection efforts, including improved satellite imagery, on-the-ground assessments, and collaboration with local entities and governments. The World Food Programme (WFP) in Kenya plays a pivotal role in addressing these challenges through targeted interventions, encompassing climate-resilient agricultural practices, conflict-sensitive food distribution, and community-based resilience-building initiatives.